Uji potensi Burkholderia cenocepacia strain KTG sebagai bahan aktif pembenah hayati pada tanah tekstur berpasir di Kalimantan Tengah The potential test of Burkholderia cenocepacia KTG strain as an active ingredient of bio-ameliorant in sandy-textured soil at Central Kalimantan - Laksmita Prima SANTI; Didiek Hadjar GOENADI (E-Journal Menara Perkebunan, 2013)
AbstractOil palm plantation at Central Kalimantan hasbeen expanded to those areas with sandy-textured soil.This type of soil has limiting factors for plant growth, i.e.unstable soil aggregation and weak organic complexbond that restrain root development and yield. However,efforts to solve this problem are very limited. Theresearch aimed to develop technology to improve theinteractions for promoting a stable soil aggregate ofsandy-textured soil. The use of exopolysaccharideproducing bacteria as a soil bio-ameliorant to mediatesandy soil micro aggregate formation by bio-augmenta-tion technique has become an accepted practice. A highlypotential endophytic bacterium for exopolysaccharidesproduction was isolated from a sandy soil located atKotawaringin Barat-Central Kalimantan. The bacteriumwas identified as Burkholderia cenocepacia KTG strain.The field experiment has been organized according to themethod of randomized complete blocks design with seventreatments of fertilizer in combination with bio-ameliorant and replicated three times. Fertilizer and bio-ameliorant application has been done in November 2009- November 2011. Field trial was evaluated based on theproduction of mature oil palm during January 2010-December 2011 periods. The data obtained indicate thatapplication of bio-ameliorant combined with reduceddosage of N-P-K 16-4-25 was not significantly differentto that of full dosage of N-P-K 16-4-25 treatment.AbstrakPengembangan perkebunan kelapa sawit diKalimantan Tengah telah masuk ke wilayah dengan tanahtekstur berpasir. Jenis tanah ini memiliki faktor pembatasbagi pertumbuhan tanaman seperti ketidakstabilan agregattanah serta ikatan organik kompleks yang lemah,sehingga perkembangan akar tanaman akan mengalamihambatan dan pada akhirnya produktivitas menjadi suboptimal. Bagaimanapun juga, upaya untuk memecahkanmasalah tersebut masih sangat terbatas. Penelitian inibertujuan mengembangkan teknologi untuk meningkat-kan kemantapan agregat tanah tekstur berpasir. Pem-bentukan mikro agregasi tanah dengan memanfaatkanbakteri penghasil eksopolisakarida sebagai pembenahhayati melalui teknik bioaugmentasi merupakan teknologiyang dapat diterapkan secara praktis di lapang. Bakteriendofitik penghasil eksopolisakarida potensial telah ber-hasil diisolasi dari tanah tekstur berpasir, di daerahKotawaringin Barat, Kalimantan Tengah. Bakteri ini di-identifikasi sebagai Burkholderia cenocepacia strainKTG. Tujuh perlakuan yang diuji merupakan kombinasipupuk dan pembenah tanah hayati dengan tiga ulangan.Aplikasi pupuk dan pembenah tanah hayati ini dilakukanselama periode Nopember 2009 - Nopember 2011.Evaluasi dilakukan atas dasar tingkat produktivitaskelapa sawit yang sudah berproduksi selama 16 tahunselama periode Januari 2010 - Desember 2011. Data yangdiperoleh menunjukkan bahwa dosis pembenah tanahyang diuji yang dikom-binasikan dengan penurunan dosispupuk N-P-K 16-4-25 tidak berbeda nyata denganperlakuan penggunaan dosis penuh pupuk N-P-K 16-4-25.